2021
DOI: 10.1136/bmjopen-2021-056487
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic effects of a prehospital emergency anaesthesia protocol consisting of fentanyl, ketamine and rocuronium in patients with trauma: a retrospective analysis of data from a Helicopter Emergency Medical Service

Abstract: ObjectivesPrehospital rapid sequence induction (RSI) of anaesthesia is an intervention with significant associated risk. In this study, we aimed to investigate the haemodynamic response over time of a prehospital RSI protocol of fentanyl, ketamine and rocuronium in a heterogeneous population of trauma patients.Design, setting and participantWe performed a retrospective study of all trauma patients who received a prehospital RSI for trauma by a physician staffed Helicopter Emergency Medical Service in the UK be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…In this cohort, fentanyl use was relatively uncommon, and the doses used were low in comparison to other published induction regimens. 21,23 There was no measurable impact of fentanyl use in the incidence of haemodynamic instability post-induction. The baseline characteristics of the two groups were similar, suggesting that other unmeasured factors such as clinician preference may be involved in the decision to use fentanyl.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In this cohort, fentanyl use was relatively uncommon, and the doses used were low in comparison to other published induction regimens. 21,23 There was no measurable impact of fentanyl use in the incidence of haemodynamic instability post-induction. The baseline characteristics of the two groups were similar, suggesting that other unmeasured factors such as clinician preference may be involved in the decision to use fentanyl.…”
Section: Discussionmentioning
confidence: 95%
“…Penetrating trauma 14 F I G U R E 2 Systolic blood pressure over time, by group limit of their first tertile being 1.24 mcg/kg, whereas the 75th centile dose in our study was 1.5 mcg/kg; this dosing discrepancy may explain the difference in our findings. Ter Avest et al also reported on a cohort of trauma patients receiving standardised dose regimens of fentanyl, ketamine and rocuronium, 23 noting a reduction in blood pressure, reaching a nadir at 6-8 min, regardless of standard or reduced dosing. The fentanyl doses used in this study were again in a higher range than in our cohort.…”
Section: Clinical Categorymentioning
confidence: 97%
See 3 more Smart Citations